Deteksi Dini Tumbuh Kembang Anak Oleh Kader di Posyandu - Lestari, Ita Puji; Lestari, Sri (UNIVERSITAS NGUDI WALUYO, 2022)
Growth and development is a process experienced by every individual where in the process physiological changes occur as a result of maturation of physical functions that take place normally. Monitoring the growth and development of toddlers is carried out every month. Children are one of the groups who feel the impact of the Covid-19 pandemic, therefore it is necessary to ensure that children's growth and development continues despite social restrictions during the pandemic so that delays in growth and development of toddlers can be overcome as early as possible. The purpose of this service is to increase efforts to monitor the growth and development of toddlers by cadres in carrying out early detection of toddler growth and development. This service method uses a cross-sectional design with the target of community service being Posyandu cadres for toddlers in the RT 7 Banyumanik area. It was found that there was an increase in cadre knowledge about the growth and development of toddlers as much as 94.5%, there was an increase in the ability to measure children's anthropometric parameters by 87.5% by cadres. It is hoped that through this service activity, posyandu cadres can be more capable and precise in measuring and detecting early growth. development of toddlers properly in order to prevent the emergence of nutritional problems in children.ABSTRAKPertumbuhan dan Perkembangan merupakan proses yang dialami oleh setiap individu dimana dalam prosesnya terjadi erubahan secara fisiologis sebagai hasil pematangan fungsi fisik yag berlangsung secara normal. Pemantauan tumbuh kembang balita dilakukan setiap bulan. Anak menjadi salah satu kelompok yang merasakan dampak dari pandemi Covid-19, oleh sebab itu perlu memastikan tumbuh kembang anak tetap berjalan meskipun pada kondisi pembatasan sosial dimasa pandemi agar keterlambatan dalam pertumbuhan dan perkembangan balita dapat diatasi sedini mungkin. Tujuan dari pengabdian ini untuk meningkatkan upaya pemantauan tumbuh kembang balita oleh kader dalam melakukan deteksi dini pertumbuhan dan perkembangan balita. Metode pengabdian ini menggunakan desain crosssectional dengan sasaran pengabdian masyarakat adalah kader posyandu balita di wilayah RT 7 Banyumanik.Hasil Pengabdian didapatkan adanya peningkatan pengetahuan kader tentang tumbuh kembang balita, dan cara melakukan pengukuran yang tepat pada parameterantropometri anak. Didapatkan terdapat peningkatan pengetahuan kader tentang tumbuh kembang balita sebanyak 94,5%, terdapat peningkatan kemampuan pengukuran parameter antrompometri anak sebanyak 87,5% oleh kader.diharapkan melalui kegiatan pengabdian ini para kader posyandu dapat lebih mampu dan tepat dalam melakukan pengukuran dan deteksi dini tumbuh kembang balita secara baik guna mencegah timbulnya masalah gizi pada anak.